Study of alkali metals and alkaline earth metals in chlorobutyl rubber-based model truck inner tube compound - Bhavani Shanker Parmar; Narendra Pal Singh Chauhan; Sapana Jadoun; Arup Saha Deuri; Dilip Vaidya; Abbas Rahdar; Narendra Singh Chundawat (Advanced Industrial and Engineering Polymer Research, 2022)
This paper describes the effects of various alkali metal and alkaline earth metal compounds, as well as walnut shell ash (WNS ash), on the cure characteristics (ts2, tc90) of a chlorobutyl rubber (CIIR)-based heat resistance truck inner tube compound. We observed that CIIR-F (KOH) has a very high scorch safety and a very slow cure. As it is a strong base with a high pH (13.84), it cures very slowly. Despite having a pH of 10.6, a ts2 of 6.36, and a tc90 of 18.84 min, CIIR-D (CaCO3) cures faster than CIIR-A (blank). The ts2 and tc90 values for CIIR-A (blank) were 6.55 and 18.88 min, respectively. Except for CIIR-D (CaCO3), all of the materials used to have higher scorch safety (ts2) and optimum cure time (tc90) in rheometer than CIIR-A (blank). CIIR-C (BaCO3) performed nearly as well as a blank. This study revealed that the trend of cure characteristics (ts2, tc90) in rheometer and Mooney scorch (t5) in Mooney viscometer not only depends on pH but also depends on ionic radius, ionization enthalpy and oxidation number of alkali metal and alkaline earth metal and the type of compound of alkali metal and alkaline earth metal.